Study of Educational Administration in Primary Schools - Ansar Ansar; Kaharman Kaharman; Yustari Yustari (Riviera Publishing, 2025)
This study examines the implementation, challenges, and strategies of educational administration at the primary school level in Makassar City. Basic education plays a crucial role in human resource development, and its effectiveness relies on quality school management. The study employs a qualitative approach, including interviews, participatory observation, and document analysis at three representative primary schools: a core public school, a peripheral public school, and a private school. The research covers eight areas of educational administration: curriculum, student affairs, educators and educational staff, facilities, finance, school-community relations, special services, and IT implementation. The findings reveal significant variation in educational administration practices across schools. Transformational leadership emerged as a key factor in successful administration, with such schools demonstrating innovation in curriculum and technology. Challenges include budget constraints affecting facility maintenance, excessive administrative workloads on teachers, and gaps in PTK’s ability to adapt to modern technology. Parental involvement in school activities remains largely ceremonial, failing to effectively support school programs. Effective strategies identified include fostering internal learning communities, forming partnerships with local businesses for facility procurement, and using simple digital platforms for communication and data management. The study concludes that improving basic education quality in Makassar requires strengthening school leadership, providing ongoing PTK training, ensuring proportional budget allocation, and implementing policies to enhance collaboration between schools, parents, and the community.